A Phase I Trial to Determine the Safety and Tolerability of Autophagy Inhibition Using Chloroquine or Hydroxychloroquine in Combination With Carboplatin and Gemcitabine in Patients With Advanced Solid Tumors - Karim, Nagla Abdel; Ullah, Asad; Ahmad, Imran; Bahassi, Elmustapha; Olowokure, Olugbenga; Khaled, Ahmed; Davis, Harold; Morris, John C. (Frontiers in Oncology, 2022)
Background Autophagy is a catabolic process that is triggered in cells during periods of metabolic or hypoxic stress, which enables their survival during this challenge. Autophagy may also impart survival advantage to tumors cells undergoing attack from chemotherapy or radiation. Inhibition of early-stage autophagy can rescue cancer cells, while inhibition of late-stage autophagy enhances cell death due to accumulation of damaged organelles. The antiparasitic drugs chloroquine (CQ) and hydroxychloroquine (HCQ) inhibit late-phase autophagy. We assessed the safety, tolerability, and efficacy of combining CQ or HCQ with carboplatin and gemcitabine (CG) in patients with refractory advanced solid tumors. Methods This single institution phase 1 dose-escalation study was designed to evaluate the maximum tolerated dose (MTD) of CQ/HCQ, in combination with CG, in patients with advanced solid tumors. Secondary objectives were to determine overall response rate (ORR), progression-free survival (PFS), and overall survival (OS). A starting dose of CQ or HCQ 50 mg was used in conjunction with standard starting doses of CG and increased in increments of 50 mg in each patient dose cohort. Grade 3 or greater toxicity that is treatment related, and was not self-limited, or not controlled in <7 days was considered dose-limiting toxicity (DLT). Results Twenty-two patients were enrolled. All patients had at least one prior treatment, and 11 of them had 3 prior regimens. CQ/HCQ 100 mg daily was found to be the MTD in combination with CG with thrombocytopenia and/or neutropenia dose limiting. The median overall (OS) was 11 months, and the 1- and 3-year OS were 30% and 7%, respectively. Median progression-free survival was 5 months, and the 6-, 12-, and 18-month progression-free survivals were 48%, 21%, and 14%, respectively. Conclusion The MTD identified for CQ/HCQ was lower than previously reported with concomitant use of chemotherapeutic regimes likely due to the myelosuppressive nature of CG in previously treated patients.